GONAD MATURITY LEVELS OF LEMPUK FISH (Gobiopterus sp) IN RANU GRATI, PASURUAN, EAST JAVA - Anitasari, Septi; Yanuhar, Uun; Faqih, Abd Rahem; Sanoesi, Ellana; Susilowati, Surya Rachman; Sansi, Delfina Husniya (Politeknik Kelautan dan Perikanan Sidoarjo, 2024)
Pasuruan Regency in East Java Province boasts a natural lake, Ranu Grati, formed by volcanic activity, covering about 50 hectares and home to endemic species like the Lempuk fish (Gobiopterus sp.). These fish play a crucial role in Ranu Grati's trophic structure, serving as primary consumers and key planktonic organisms supporting higher trophic levels. The Lempuk fish population faces sustainability challenges due to high demand for this traditional food, leading to overexploitation and decreased reproductive capabilities. Understanding the reproductive biology, particularly gonad maturity levels, is vital for effective resource management. This study, conducted from June to August 2023, aimed to investigate the reproductive biology and gonad maturity levels of Lempuk fish in Ranu Grati. Analysis revealed a male-biased sex ratio, with significant fluctuations in gonad maturity levels across months. In June, the sex ratio was 1.05, in July 1.17, and in August 1.39, indicating a higher population of males. Histological observations showed asynchronous egg development, likely influenced by environmental factors and the fish's reproductive strategy